English, asked by adityasinghtheking7, 5 months ago

Please Answer Please.​

Attachments:

Answers

Answered by nahmishg
7

Answer:

give thanks for me ndjdjjdjdjsis

Answered by IamSpecial
13

Answer:

3x - 4y = 5

Cubing both sides,

(3x - 4y)³ = 5³

Applying the formula,(a - b)³ = a³ - b³ - 3ab(a - b)

(3x)³ - (4y)³ - 3 × 3x × 4y × (3x − 4y) = 125

(3x)³ - (4y)³ - 36 × xy × (3x - 4y) = 125

Substituting,3x - 4y = 5 ; xy = 3

27x³ - 64y³ - 36 × 3 × 5 = 125

27x³ - 64y³ = 125 + 540 = 665

HOPE IT HELPS!!!

PLEASE MARK AS BRAINLIEST!!!

Similar questions